A Rare Presentation of Isolated CNS Posttransplantation Lymphoproliferative Disorder. (2nd January 2017) - Morris, Jaime; Smith, Casey; Streicher, Andrew; Magnuson, Allison; Newman, Susan; Bertoli, Robert
Abstract : Posttransplantation lymphoproliferative disorder (PTLD) is a recognized and extremely morbid complication of solid organ transplantation, but central nervous system involvement, particularly in isolation, is rare. There are no standardized treatment strategies for PTLD, though commonly used strategies include reduction of immunosuppression, chemotherapy, rituximab, radiation, and surgery. We present a case of an unusual morphologic variant of primary central nervous system PTLD with successful response to rituximab and cranial radiation. A 69-year-old Asian male, who underwent postrenal transplant nine years earlier, presented with a one-month history of new onset seizure activity. His evaluation revealed multiple brain lesions on magnetic resonance imaging (MRI), as well as serologic and cerebrospinal fluid studies which were positive for Epstein-Barr Virus (EBV) infection. Ultimately, he underwent craniotomy with tissue biopsy with the final pathology report showing posttransplant lymphoproliferative disorder, polymorphic type. The patient was managed with reduction in immunosuppression, rituximab therapy, and cranial radiation treatments. He had demonstrated marked improvement in his neurologic function and was ultimately discharged to inpatient rehabilitation facility.